Antikvarianisme på norsk - Eriksen, Anne (Tidsskrift for kulturforskning, 2014)
Iver Wiel’s Beskrivelse over Ringeriges og Hallingdalens Fogderi (Description of the bailiwick of Ringerike and Hallingdal) from 1743 differs in significant ways from the numerous topographic texts that were published in Denmark-Norway in the second half of the eighteenth century. It is above all distinguished by Wiel’s strong antiquarian and historical interests, which made him fill the text with information on ancient monuments and popular traditions. The article presents an investigation of Wiel’s antiquarian work, in particular his discussions of some large drinking horns owned by peasants in Hallingdal.